Population density of Saguinus leucopus (Mammalia: Primates) and landscape characteristics in eastern Antioquia, Colombia - Bonell Rojas, William Yezid; Alvarez Rincon, Mario Alberto; Roncancio Duque, Nestor Javier (THERYA, 2018)
Saguinus leucopus is an endemic primate of Colombia, listed as an â€œEndangeredâ€ species by IUCN because of its restricted distribution range in areas with intense colonization activity. Population density is a key factor in understanding the trends of S. leucopus populations after disturbance by the anthropogenic transformations of the landscape. Density is determined by its carrying capacity, being a dynamic parameter that varies in time and space. The trends in certain populations are inconclusive, as assessments were performed just one in a few sites. Besides, knowing the variables that govern the changes in population size as well as its regulation is important, starting with an empirical estimate of the number of individuals in populations. The objectives of this study were to estimate the population density of S. leucopus and determine its relationship with plant diversity and landscape characteristics. This study was developed in a forest, located in the municipality of San Rafael, Antioquia. The population density of S. leucopus was estimated using the distance-sampling method with linear transects; data were processed with the program DISTANCE 6.0. The physical features, structure and diversity of plant communities were also determined. The estimated population density of S. leucopus was 46.5 individuals/km2 and 12.3 groups/km2, with coefficients of variation of 19.2 % and 16.8 %, respectively. The component with the major contribution to the variance of density was the encounter rate, with 64.7 %. The study area is an open forest with moderate connectivity and a tendency to be circular; the vegetation cover is relatively homogeneous, being in the same stage of natural regeneration across its area. The estimated population density of S. leucopus is within the average reported for the species. Populations of S. leucopus tend to vary significantly according to the particular features of the local environment. In order to estimate the conservation status of the species through the analysis of variations in population density, this type of work should be linked to a monitoring strategy. In the study area, human activities over time have been key in determining the structure of the current vegetation. The population studied meets all the requirements to be in a good condition, since the continuous forest is protected and artificial structures built on-site allow the white-footed tamarin to forage and move; thus, it can be inferred that local populations inhabiting the study area are not isolated.